Strategi Duta Wisata Dalam Mempromosikan Pariwisata Di Kabupaten Brebes - Zumaeroh Zumaeroh; Sodik Dwi Purnomo; Bagus Adhitya; Damar Jati (Majalah Imiah Manajemen & Bisnis, 2022)
The development of tourism in Kabupaten Brebes has obstacles and obstacles that must be faced, especially if it is not supported by the community around the tourist attractions. This study aims to determine the strategy of Kabupaten Brebes in promoting tourism. This research is a qualitative research that describes in depth the object of research through interviews, documentation, and literature studies. The results of this study indicate that the implementer of tourism development goals, the Tourism Information Center, and as a media liaison between the community and tourism managers. The results of this study are expected to be input for Kabupaten Brebes and other Regencies in developing tourism development strategies